2008
DOI: 10.3144/expresspolymlett.2008.88
|View full text |Cite
|
Sign up to set email alerts
|

Nanofilled and/or toughened POM composites produced by water-mediated melt compounding: Structure and mechanical properties

Abstract: Abstract. Binary and ternary composites composed of polyoxymethylene (POM), polyurethane (PU) and synthetic boehmite alumina (AlO(OH)) were produced by water-mediated melt compounding technique. PU latex and/or aqueous alumina suspension were injected into the molten POM in a twin-screw extruder to prepare toughened and/or reinforced polymer composites. The dispersion of the alumina and PU was studied by transmission-and scanning electron microcopy techniques (TEM and SEM, respectively), and discussed. The cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 19 publications
(23 reference statements)
5
28
1
Order By: Relevance
“…It is rather suggested that the presence of the filler disturbs the amorphous-crystal interface in such a way that the nanofiller acts like a stretching agent for the chains located at the interface. Regarding that the crystallinity of the specimens, examined in the present work, is not affected by the inclusion of the filler [20], a similar interpretation can be adopted for the α-peak shift observed in our measurements.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…It is rather suggested that the presence of the filler disturbs the amorphous-crystal interface in such a way that the nanofiller acts like a stretching agent for the chains located at the interface. Regarding that the crystallinity of the specimens, examined in the present work, is not affected by the inclusion of the filler [20], a similar interpretation can be adopted for the α-peak shift observed in our measurements.…”
Section: Resultssupporting
confidence: 68%
“…Shift of the α-peak to higher temperatures, has been previously observed for POM following annealing, attributed to the increase of the crystallite size [6,22]. Nevertheless, previous morphological and thermal studies on POM/alumina systems, similar to the one studied in the present work, do not indicate any change in the crystalline structure of POM due to the incorporation of the alumina slurry [20]. As a result we cannot attribute the shift of α-peak to crystallinity changes.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…A similar approach was proposed by Siengchin et al. to obtain toughened POM nanocomposites [29]. Besides, polyethers are reported to favor the untreated clay layers intercalation.…”
Section: Introductionmentioning
confidence: 79%
“…Short-time creep tests were carried out using the methodology described by Siengchin and Karger-Kocsis [43,44] , in a DMA Q800 apparatus (TA Instruments), using the tensile mode at 25 °C. The creep and recoverable compliance were determined as a function of time (t creep = 10 minutes and t recovery = 30 minutes) It was applied a tensile stress of 0.1 MPa.…”
Section: Characterization and Testingmentioning
confidence: 99%